(4i)(-8+8i)=

Simple and best practice solution for (4i)(-8+8i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4i)(-8+8i)= equation:


Simplifying
(4i)(-8 + 8i) = 0

Remove parenthesis around (4i)
4i(-8 + 8i) = 0
(-8 * 4i + 8i * 4i) = 0
(-32i + 32i2) = 0

Solving
-32i + 32i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '32i'.
32i(-1 + i) = 0

Ignore the factor 32.

Subproblem 1

Set the factor 'i' equal to zero and attempt to solve: Simplifying i = 0 Solving i = 0 Move all terms containing i to the left, all other terms to the right. Simplifying i = 0

Subproblem 2

Set the factor '(-1 + i)' equal to zero and attempt to solve: Simplifying -1 + i = 0 Solving -1 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + i = 0 + 1 Combine like terms: -1 + 1 = 0 0 + i = 0 + 1 i = 0 + 1 Combine like terms: 0 + 1 = 1 i = 1 Simplifying i = 1

Solution

i = {0, 1}

See similar equations:

| 5.3x=4.1x+5.76 | | 2.5h+.5(h-1)=-12.5 | | 5x-9=-3x+12+5x | | 7/12=x60 | | 1/8x-9=17 | | 3x+6=8x-49 | | 2x-3(5-3x)=7x+3 | | .3+.2(g+7)=1.5 | | -0.005q^2+2.5q=300 | | 11*y=77 | | 3x+6=10x+3 | | Hg(x)=2g(x) | | (5x-1)/x=1 | | -40(-28/3) | | .1(f-7)+.05f=.8 | | -(x+3)=2+7 | | log32b=-1/4 | | 42=3w-9 | | 3x+2(3)=4 | | 5-3x=-4[3(x+2)-1] | | 7d=4+6d | | 2(-14/3)-40 | | 9y+4=8y-5 | | -2v/9=-12 | | 8=y/25.6 | | .4(e+5)-.3e=17 | | (5x-1)/1=1 | | 8(4-x)=4(x+5) | | 3x-6.2=14.2 | | -8d=-9d+7 | | 30=-5/2u | | 90=(x+2)(y+1.5) |

Equations solver categories